2013
DOI: 10.1152/ajpgi.00281.2012
|View full text |Cite
|
Sign up to set email alerts
|

A PKG inhibitor increases Ca2+-regulated exocytosis in guinea pig antral mucous cells: cAMP accumulation via PDE2A inhibition

Abstract: In antral mucous cells, acetylcholine (ACh, 1 M) activates Ca 2ϩ -regulated exocytosis, consisting of an initial peak that declines rapidly (initial transient phase) followed by a second slower decline (late phase) lasting during ACh stimulation. The addition of 8-bromo-cGMP (8-BrcGMP) enhanced the initial phase, which was inhibited by the protein kinase G (PKG) inhibitor guanosine 3=,5=-cyclic monophosphorothoiate, ␤-phenyl-1,N 2 -etheno-8-bromo, Rp-isomer, sodium salt (Rp-8-BrPETcGMPS, 100 nM). However, Rp-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…The Ca 2+ -regulated exocytotic events is characterized by an initial peak in exocytotic events that declined rapidly (initial phase) followed by a second slower decline (late phase) lasting during ACh stimulation (8,9,14,19,(21)(22)(23)(24). In a previous study (28), an increase in NO/cGMP stimulated by PPARα enhanced the initial phase of Ca 2+ -regulated exocytotic events in antral mucous cells and a NOS1 inhibitor (N-PLA) or a PKG inhibitor (Rp8BrPETcGMPS) abolished the enhancement of the initial phase and produced the delayed, but transient, increase in the late phase (27,28). The similar experiments were carried out using GW7647, GW6471, and ACh in this study.…”
Section: Effects Of Wortmannin and Akt-inh On Ach-stimulated Exocytotmentioning
confidence: 89%
See 4 more Smart Citations
“…The Ca 2+ -regulated exocytotic events is characterized by an initial peak in exocytotic events that declined rapidly (initial phase) followed by a second slower decline (late phase) lasting during ACh stimulation (8,9,14,19,(21)(22)(23)(24). In a previous study (28), an increase in NO/cGMP stimulated by PPARα enhanced the initial phase of Ca 2+ -regulated exocytotic events in antral mucous cells and a NOS1 inhibitor (N-PLA) or a PKG inhibitor (Rp8BrPETcGMPS) abolished the enhancement of the initial phase and produced the delayed, but transient, increase in the late phase (27,28). The similar experiments were carried out using GW7647, GW6471, and ACh in this study.…”
Section: Effects Of Wortmannin and Akt-inh On Ach-stimulated Exocytotmentioning
confidence: 89%
“…The frequencies of initial phase and late produced a delayed, but transient, increase in the late phase stimulated by GW7647 plus ACh (4.5 ± 0.7 events/cell/30s, n = 11). A previous study demonstrated that antral mucous cells have cGMP-dependent PDE2 and the PDE2 inhibited by BAY60-7550 (a selective inhibitor of PDE2) produces the delayed, but transient, increase in the late phase (27). BAY60-7550 induced cAMP accumulation and the delayed, but transient, increase in the late phase was abolished by PKI-amide (1 μM, a PKA inhibitor).…”
Section: Effects Of Wortmannin and Akt-inh On Ach-stimulated Exocytotmentioning
confidence: 95%
See 3 more Smart Citations